2018
DOI: 10.1038/s41598-018-33127-1
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic marine ciliates under stress: superoxide dismutases from the psychrophilic Euplotes focardii are cold-active yet heat tolerant enzymes

Abstract: Oxidative stress is a particularly severe threat to Antarctic marine polar organisms because they are exposed to high dissolved oxygen and to intense UV radiation. This paper reports the features of three superoxide dismutases from the Antarctic psychrophilic ciliate Euplotes focardii that faces two environmental challenges, oxidative stress and low temperature. Two out of these are Cu,Zn superoxide dismutases (named Ef-SOD1a and Ef-SOD1b) and one belongs to the Mn-containing group (Ef-SOD2). Ef-SOD1s and Ef-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…As reported previously (Watanabe et al 2005), the mesophilic AvIDH showed high specific activities at low temperatures such as 10˚C rather than the coldadapted PmIDH, implying that the thermolability of the enzyme proteins is not necessary for high catalytic activity at low temperatures. On the other hand, in cold-active and thermostable superoxide dismutases from psychrophilic Pseudoalteromonas haloplanktis and Euplotes focardii, their cold activities were suggested to be achieved by the increased local flexibility of their active sites (Merllino et al 2010;Pischedda et al 2018). This mechanism might be explaining the activity of AvIDH at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously (Watanabe et al 2005), the mesophilic AvIDH showed high specific activities at low temperatures such as 10˚C rather than the coldadapted PmIDH, implying that the thermolability of the enzyme proteins is not necessary for high catalytic activity at low temperatures. On the other hand, in cold-active and thermostable superoxide dismutases from psychrophilic Pseudoalteromonas haloplanktis and Euplotes focardii, their cold activities were suggested to be achieved by the increased local flexibility of their active sites (Merllino et al 2010;Pischedda et al 2018). This mechanism might be explaining the activity of AvIDH at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In the marine ciliate E . focardii and the amoeba Acanthamoeba castellani , the enzymes Cu/ZnSODs are homodimeric 26,58 . The low homology between the AA sequences of the Cu/Zn-SOD in P .…”
Section: Discussionmentioning
confidence: 99%
“…The Fe- and Mn-SOD enzymes are the oldest SOD group and have probably evolved from orthologous genes 20 . Fe-SOD enzymes are found in prokaryotes and in chloroplasts, while Mn-SODs occur both in prokaryotes and in the mitochondrial matrix of eukaryotes 26 . It has been suggested that iron may have been the first metal used as a cofactor associated with the active site of the first SOD due to its abundance at that time in the form of soluble Fe 2+ 65 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations